The deformation mechanism of gallium-faces and nitrogen-faces gallium nitride during nanogrinding. (15th January 2022) - Zhang, Chaoyue; Dong, Zhigang; Zhang, Shuohua; Guo, Xiaoguang; Yuan, Song; Jin, Zhuji; Kang, Renke; Guo, Dongming
Highlights: Studied the deformation mechanism of N-faces and Ga-faces GaN in nanogrinding. Using MD simulation to research the nanogrinding process of GaN from atomic scale. Found the distinct of force, temperature, dislocation and MMR between Ga- and N-faces. The reason why N-faces has more dislocations than Ga-faces was found. Abstract: In this study, the deformation mechanism of gallium-faces (Ga-faces) and nitrogen-faces (N-faces) gallium nitride (GaN) during nanogrinding were investigated by molecular dynamics (MD). The differences between the two were analyzed from force, temperature, potential energy, surface/subsurface damage, and material removal rate (MRR). The results show that N-faces GaN withstand lower grinding force, higher temperature, potential energy, and MRR. Meanwhile, the total length of dislocations and the number of zinc blende phase atoms are also greater than those in Ga-faces. Further research found that the difference in edge dislocation with b = 1/3 〈11–20〉 is the main reason that causes the dislocations in N-faces longer than that in Ga-faces, which can reach about 3 times. However, the Shockley incomplete dislocation with b = 1/3 〈1–100〉 and other dislocations are slightly smaller than those in Ga-faces. This study innovatively researched the difference in the processing properties of the two GaN at the nano-scale, which provide a theoretical basis for guiding GaN in the processing of ultra-precision. Graphical abstract: Image, graphical abstract